New Representative of the Family Hydroscaphidae from Tunguska Basin, the Boundary of the Permian and Triassic (Coleoptera, Myxophaga) with Review on Myxophagan Fossil R ecords (Global Journal of Science Frontier Research, 2023)
Palaeoscapha tunguskaensis gen et sp nov the oldest representative of the family Hydroscaphidae is described from the Tunguska Basin in Siberia dated from the boundary of the Permian and Triassic It is assigned to the subfamily Triamyxinae stat nov New diagnoses of the Hydroscaphidae and Triamyxinae are proposed The new subfamily Leehermaniinae subfam nov type genus Leehermania is erected The fossil record of the suborder Myxophaga is reviewed and revised with some taxonomic notes and synonymy of some generic and species names in the family Lepiceridae known from Burmese amber Different aspects of the evolutionary history of this suborder are discussed A synonymy of Haplochelus and Lepiceratus is proposed
Keywords: Lepiceridae; Spheriusidae; Torridincolidae; Triamixinae; Leehermaniinae; evolutionary history; new subfamily